INFLUENCE OF SOFT: SQUEEZING ON THE AXIAL CHEMICAL HETEROGENEITY DEGREE AT PRODUCTION OF CONTINUOUSLY-CASTED INGOTS. Message 2. Mathematical modeling and analysis of the results - Ju. A. Samojlovich; V. I. Timoshpolskij; I. A. Trusova; N. L. Mandel (Литьë и металлургия, 2008)
Mathematical model and results of calculation analysis on determination of influence of ‘'soft squeezing” on degree of axial chemical heterogeneity(distribution of carbon, sulfur and manganese) in billets, produced by means of continuous casting, are given.